Emotional states classification from brain signals - Lee, Vinson Bing Jun. (2013)
Electroencephalography (EEG) signal analysis is very useful in the assessment of emotion mechanisms. With the study of emotions, it can gradually lead to integration with the Human-Computer Interaction (HCI) systems. In this project, these signals were generated by visual stimuli and are collected. The EEG signals were obtained using four electrode placements, according to 10-20 systems, from 5 subjects with 30 samples each. The time-domain and frequency-domain features of these signals are culled with a MATLAB algorithm.